Bone density and marginal bone loss around implants post ultraviolet A and ultraviolet C irradiation - Zaheer, Naauman; Zainul Ahmad Rajion,; Shahbaz, Maliha; Zaheer, Usman; Saeed, Muhammad Qasim; Noor Hayati Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this paper was to evaluate marginal bone loss (MBL) and bone density (BD) in the alveolar bone surrounding the titanium implants with or without ultraviolet (UV) pre-treatment at different wavelengths in vivo. Randomized control trial conducted at the CMH Lahore Medical College, Institute of Dentistry. This interventional study enrolled patients undergoing replacement of missing teeth. Sixty-six Dio UFII implants with hybrid sandblasted and acidetched (SLA) surface treatments were divided equally into three groups. Control Group A was not irradiated, while implants in groups B and C were irradiated with UVA (382 nm, 25 mWcm2) and UVC (260 nm, 15 mWcm2), respectively. MBL and BD in the surrounding bone were evaluated at day 0 (baseline) and 8th and 26th week. SPSS 20.0 was used for data analysis. Repeated measure ANOVA followed by One-way ANOVA, Tukey’s test and Paired t-test were used for comparison. p ≤ 0.05 was considered statistically significant. Both UVA and UVC treated groups showed minimal MBL compared to control group, with no significant difference between the two experimental groups. Meanwhile, there was a steady increase in BD in all groups over time, with UVC showing a significant improvement between the 8th and 26th week. MBL was reduced and BD was increased in both UV treated groups. However, UVC irradiation has the potential to control MBL and produce denser bone in SLA coated implants.